Fiction books translations for children: publishing in Lithuania in 1940-1990 - Vita Mozūraitė (Knygotyra)
Translated literature comprises a significant portion of all children's books in Lithuania. Often, works originally written for adults become popular as children's literature worldwide (e.g., D. Defoe's, J. Swift's, A. Dumas', Ch. Perrault's, and others). As a result, many book editors face difficulties in determining the appropriate target audience for these books. Consequently, the same classic literary work, published in Lithuania at different times, may be aimed at various reader groups (for example, "Robinson Crusoe").